A REVIEW OF CURRENT CONCEPTS IN BRUXISM – DIAGNOSIS AND MANAGEMENT - D., Krishna Prasad; Swaminathan, Archana Ashok; D., Anupama Prasad (Journal of Health and Allied Sciences NU, 2014)
Bruxism, which can be considered as an umbrella term for clenching and grinding of teeth, is the commonest of the many parafunctional activities of the stomatognathic system. Bruxism can occur during wakefulness or during sleep and each has a different set of causative factors. The early diagnosis and management can prevent the breakdown of the dentition and pain in the orofacial region. Although various treatment modalities are present, the successful management of bruxism lies in the precise diagnosis and isolation of the etiology.
Keywords: Bruxism; Sleep bruxism; Awake bruxism; Current concepts in bruxism; Review of bruxism